Peluang Dan Tantangan Pengembangan Layanan Wisata Kapal Pesiar (Cruise) Di Pelabuhan Belawan Medan - I Made Adhi Gunadi (Samarinda State Polytechnic, 2020)
As an archipelago, Indonesia has huge potential to become a marine tourism destination, including cruise tourism. Cruise tourism is a very segmented tour and has developed into a complete, complex tourism business and at the same time being able to make a significant and promising contribution in the global tourism industry. This study seeks to assess the readiness of the Belawan port in providing support services to the complex cruise tourism. As an analysis tool, the approach of Manzano (2014) was used. The results of the study show that Belawan already has sufficient readiness to support cruise tourism, but also faces significant challenges so that the services provided can run continuously.